A Patient With Graves’ Disease And Thyroid-Associated Orbitopathy Undergoing Radioactive Iodine in Dr. Soetomo General Academic Hospital, Surabaya - Rizki Adrian Hakim; Stepanus Massora; Delfitri Lutfi; Hermina Novida (Biomolecular and Health Science Journal, 2021)
Graves’ Disease (GD) is the most common etiology of thyrotoxicosis, followed by toxic multinodular goiter and toxic adenoma. GD can be managed with anti-thyroid drugs (ATDs), surgery, or radioactive iodine (RAI). Thyroid-associated orbitopathy (TAO) or Graves’ Ophthalmopathy (GO) affects 25%-50% patients with GD, and its presence usually dissuade clinicians to use RAI in treating hyperthyroidism. The presence of GO is a relative contraindication use of RAI in patients with GD, as RAI can worsen existing GO. Corticosteroid prophylaxis can be given to such patients to reduce likelihood of worsening of GO. However, patient with moderate to severe active GO is currently advised against undergoing RAI. Established guidelines recommend the use of corticosteroid prophylaxis in these patients. We reported a patients with GD and orbitopathy who was treated with RAI and was given steroid prophylaxis to prevent worsening of GO.